MANAJEMEN LABA PADA PERUSAHAAN MANUFAKTUR:SUATU KAJIAN EMPIRIS - Fitriani, Dwi; Sulistyawati, Ardiani Ika (Fakultas Ekonomi, Universitas Semarang, 2022)
Earnings management is an action taken by management that can increase or decrease profits, a step taken by the company to get as much profit as possible in the midst of high business competition. This study analyzes the Factors Affecting Profit Management in Manufacturing Companies. The influencing factors in this study include: leverage, company size, independent commissioner, audit committee, audit quality. The research sample used in this study was 232 manufacturing companies listed on the Indonesia Stock Exchange for the period 2015-2017. The sample was chosen based on the purposive sampling method according to the criteria contained in this study and using multiple linear analysis models. As per the results of the study, it proves that all independent variables can only explain 44.6% of the dependent variable. Independent commissioner variables and audit quality have no effect on earnings management. While the leverage variable, company size, and audit committee influence earnings management.Keywords: earnings management, leverage, company size, independent commissioner, audit committee, audit quality